Integration of the river ecosystem attributes for river health assessment - Eh Rak, Aweng (2013)
Currently in Malaysia, only physical and chemical components are used as an indicator for river health monitoring and rehabilitation programme. These attributes were used for many years as a basis and reference in rehabilitating rivers in Malaysia and none of them was proven to be successful. Therefore, the aim of this study is to integrate the river ecosystem attributes for the purpose of river health assessment in Malaysia by using benthic macroinvertebrate as the main biological indicator. This study was conducted in Sungai Mengkibol, Sungai Madek and Sungai Dengar in Johor. There were a total of five sampling sites, three for impact stations and two as reference stations, including one highland station. The sampling was conducted six times during November 2008 to June 2010. Surber Net measuring 500 micron mesh size combined with a rectangular quadrate of 30 cm x 30 cm (0.09 m2) were used to sample the benthic macro-invertebrate. Biodiversity Indices was also analyzed. For water quality, six in-situ parameters were measured namely temperature, conductivity, dissolved oxygen (DO), pH, turbidity and salinity using a multi parameter probe as well as a single parameter probe. Meanwhile, field survey form was used to assess river habitat namely river riparian compositions, canopy cover and large woody debris. In addition, Pebble Count Method was used to measure substrate compositions and Valeport ‘Braystoke’ Model 001 Flow Meter was used to gauge the river. Based on the results obtained from the study, it can be suggested that ephemeroptera, plecoptera, and trichoptera index (EPT) taxa could be used as biological indicator for preliminary river health assessment. However, for the detail assessment, physicochemical water quality, river discharge, channel deformation, substrate compositions, riparian and canopy cover and large woody debris need to be evaluated and integrated.